The effects of vocational education on adult skills and wages : what can we learn from PIAAC? - Brunello, Giorgio [Verfasser]; Rocco, Lorenzo [Verfasser] (OECD Publishing, 2015)
"Vocational education and training are highly valued by many. The European Ministers for Vocational Education and Training, the European Social Partners and the European Commission have issued in 2010 the Bruges Communiqué, which describes the global vision for VET in Europe 2020. In this vision, vocational skills and competencies are considered as important as academic skills and competencies. VET is expected to play an important role in achieving two Europe 2020 headline targets set in the education field: a) reduce the rate of early school leavers from education to less than 10 percent; b) increase the share of 30 to 40 years old having completed tertiary or equivalent education to at least 40 percent. However, there is limited hard evidence that VET can improve education and labour market outcomes. The few existing studies yield mixed results partly due to differences in the structure and quality of VET across countries. This report investigates the effects of VET on adult skills and labour market outcomes by using the PIAAC survey. Data comparability across countries, the breath of countries involved, and the almost unique presence of information on assessed skills, training, earnings and employment makes this survey especially valuable to study the different facets of VET as compared to more academic education." (Authors' abstract, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.2 Europa; Berufsbildung; Bildungsabschluss; Arbeitsmarktchance; Kompetenzentwicklung; Grundbildung; PIAAC; Europa; Internationaler Vergleich